RANCANG BANGUN SMART GROW BOX HIDROPONIK UNTUK PERTUMBUHAN TANAMAN MICROGREEN BERBASIS INTERNET OF THINGS - Revan Haidar Hilmy; Ratna Susana; Febrian Hadiatna (Politeknik Harapan Bersama Tegal, 2021)
Abstract - Smart Grow Box is a place that is used as a medium for growing microgreen plants with an indoor system. In this study, a hydroponic Smart Grow Box was designed for smartphone-based microgreen plant growth. This study aims to monitor and control the environmental parameters of microgreen plant growth in the grow box that has been made. The system is designed using the DHT22 sensor as a temperature and humidity reader and the RTC DS3231 as a time control. The output from the sensor and RTC will be processed by the ESP32 microcontroller unit which is then forwarded to the system actuators and smartphones via the internet. This system designed uses the Blynk App application which can perform monitoring and control processes remotely based on the internet of things. This Smart Grow Box can reduce air humidity up to 4.71% lower than room air humidity, can increase air humidity to 90% within 54 seconds, and can lower air temperature close to room air temperature by a difference of 0.07 ℃. Smart Grow Boxes can also increase the quality of microgreen harvests by up to 40%.